2003
DOI: 10.1021/jf030333q
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Natamycin and Its Cyclodextrin Inclusion Complexes in Aqueous Solution

Abstract: Aqueous solutions of natamycin and its beta-cyclodextrin (beta-CD), hydroxypropyl beta-cyclodextrin, and gamma-cyclodextrin (gamma-CD) inclusion complexes were completely degraded after 24 h of exposure to 1000 lx fluorescent lighting at 4 degrees C. After 14 days of storage in darkness at 4 degrees C, 92.2% of natamycin remained in active form. The natamycin:beta-CD complex and natamycin:gamma-CD complex were significantly more stable (p < 0.05) than natamycin in its free state in aqueous solutions stored in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 17 publications
(16 reference statements)
1
52
0
Order By: Relevance
“…If the speed is too high, then natamycin outflows the column before being combined with the column, thereby reducing the recovery. However, if the speed is too low, then the exposure time of natamycin increases, leading to light degradation, thus reducing the recovery (Budavari, 1989;Koontz, Marcy, Barbeau, & Duncan, 2003;Roberts et al, 2011). Five rates were tested, and the result is shown in Fig.…”
Section: Optimization Of the Spe Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the speed is too high, then natamycin outflows the column before being combined with the column, thereby reducing the recovery. However, if the speed is too low, then the exposure time of natamycin increases, leading to light degradation, thus reducing the recovery (Budavari, 1989;Koontz, Marcy, Barbeau, & Duncan, 2003;Roberts et al, 2011). Five rates were tested, and the result is shown in Fig.…”
Section: Optimization Of the Spe Conditionsmentioning
confidence: 99%
“…First, natamycin might degrade in the wines. Koontz et al (2003) reported that the aqueous solutions of natamycin was completely degraded after 24 h of exposure to 1000 lx fluorescent lighting at 4°C, while after 14 days of storage in the dark at 4°C, 92.2% of natamycin remained in active form. Brik (1976) reported that in wines, the degradation product of natamycin might be mycosamine or trehalosamine.…”
Section: The Stability Of Natamycin In Winementioning
confidence: 99%
“…In addition, this assay is used to assess the capacity of nanohydrogels to protect the pimaricin by keeping it chemically stable under favourable (A) and unfavourable (B) conditions since critical amounts of pimaricin could be degraded under acidic conditions [183] and fluorescent lighting. Koontz et al [99] addressed this problem and studied how forming inclusion complexes of pimaricin and cyclodextrins increased the stability of pimaricin compared to free pimaricin in cheese products stored under high-intensity fluorescent lighting in supermarket freezer showcases.…”
Section: Inhibition Studies Employing Food Model Systemsmentioning
confidence: 99%
“…It seems that, regardless of temperature, the conditions provided by the grape juice (pH 3.5) more importantly affect the degradation of pimaricin. Because, at low pH values, pimaricin is rapidly degraded, producing mycosamine by hydrolysis of the glycosidic bond [99].…”
Section: Statistical Analysis Antimicrobial Effectiveness Amongst Trmentioning
confidence: 99%
“…It has been approved as a food additive in over 40 countries and has been considered as a Generally Recognized. As Safe (GRAS) product by Food and Drug Administration (FDA) [6] and also indicated as a natural preservative by the European Union (EU). Natamycin (Pimaricin) (Figure 1), a polyene macrolide antibiotic, is a potent antifungal compound that can effectively prevent the growth of yeasts and inhibit aflatoxine formation in molds [7].…”
Section: Introductionmentioning
confidence: 99%